Commercial utilization of mineral waste: review of analysis methods determining its compliance with environmental laws - Gruszecka-Kosowska, Agnieszka; Mikoda, Bartosz (Geology, Geophysics and Environment, 2016)
Optimal methods used in the analysis of waste material resulting from mining and processing of mineral resources that allow to assess the potential impact of waste on the environment, based on binding environmental laws regulating potential commercial utilization of waste were investigated . The paper is concerned mostly with mineral waste, constituting about 80% of all industrial waste generated. According to the principles of sustainable waste management, waste storage is considered to be the last resort. However, every year over 20% of the total amount of industrial waste generated is stored, which makes the amount of the already deposited materials, coming from the time when the commercial utilization was not common in Poland, even more considerable. When it comes to extensive, i.e. regarding great quantities, and long-term usage of industrial wastes, the identical composition of waste material coming from different batches is of the essence. Unfortunately, this condition is not always fulfilled, therefore chemical composition analyses need to be carried out for monitoring purposes. For the same reason the waste material used should also be tested to check whether the parameters of a given batch are within the limit values defined by the standards. Described methods are intended to facilitate waste characterisation with respect to their effect on the environment when used for commercial purposes. An individual method is never good enough to determine the full extent of environmental impact. It is therefore recommended to apply several methods in a logical sequence, depending on the type of waste material and its purpose.